2007
DOI: 10.3349/ymj.2007.48.3.405
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroradiological Findings of Children with Developmental Language Disorder

Abstract: PurposeTo investigate the general characteristics of glucose metabolism distribution and the functional deficit in the brain of children with developmental language delay (DLD), we compared functional neuroradiological studies such as positron emission tomography (PET) of a patient group of DLD children and a control group of attention-deficit hyperactivity disorder (ADHD) children.Patients and MethodsSeventeen DLD children and 10 ADHD children under 10 years of age were recruited and divided into separate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
3
10
0
2
Order By: Relevance
“…First, imaging techniques are one of the most direct approaches to examine the basal ganglia in the human brain. In previous research, there were a few studies looking at abnormal structures and functions of the brain in individuals with DLI (Badcock et al, 2012; Friederici, 2006; Hugdahl et al, 2004; Hwang et al, 2006; Im et al, 2007; Ors et al, 2005); however, none of the imaging studies of DLI looked at the structures of the basal ganglia based on an established hypothesis. Therefore, further studies are needed to explore the role of the basal ganglia regions in individuals with DLI.…”
Section: Discussionmentioning
confidence: 99%
“…First, imaging techniques are one of the most direct approaches to examine the basal ganglia in the human brain. In previous research, there were a few studies looking at abnormal structures and functions of the brain in individuals with DLI (Badcock et al, 2012; Friederici, 2006; Hugdahl et al, 2004; Hwang et al, 2006; Im et al, 2007; Ors et al, 2005); however, none of the imaging studies of DLI looked at the structures of the basal ganglia based on an established hypothesis. Therefore, further studies are needed to explore the role of the basal ganglia regions in individuals with DLI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that individuals with DLI had abnormalities in the basal ganglia (Im et al, 2007;Ors et al, 2005), particularly in the caudate nucleus (Badcock et al, 2011;Herbert et al, 2003;Jernigan et al, 1991;Soriano-Mas et al, 2009;Tallal et al, 1994;Watkins et al, 2002) and in the putamen (Badcock et al, 2011;Hwang et al, 2006;Watkins et al, 2002). The current findings are consistent with findings from previous research, demonstrating abnormalities not only in the putamen but also in the globus pallidus and in the nucleus accumbens.…”
Section: Abnormality Of Basal Ganglia Substructures In DLIsupporting
confidence: 92%
“…In terms of functional neuroimaging studies, researchers reported abnormal activities within several cortical regions, including frontal, temporal, and parietal areas, while individuals with DLI performed language-related tasks (Friederici, 2006;Hugdahl et al, 2004;Ellis Weismer et al, 2005). Im et al (2007) showed abnormal findings in children with DLI on positron emission tomography (PET) scans, and the abnormalities were confined to the thalamus, the basal ganglia, the cerebellum, and the frontal lobes, despite that brain structures of these children appeared normal in the conventional MRI scans.…”
Section: Developmental Language Impairment (Dli)mentioning
confidence: 99%
“…It includes 56 items each for evaluation of receptive and expressive language, and provides results as either standard scores as a percentile or equivalent ages (months) compared to that of a peer group. The SELSI has been widely used for evaluation of language development in Korean infants and children [17][18][19].…”
Section: Discussionmentioning
confidence: 99%